RDA (Resource Description and Access) ? nowy standard katalogowania i jego wdrażanie w bibliotekach polskich = RDA (Resource Description and Access) ? a new standard for cataloging and its implementation in Polish libraries - Chocianowska-Sidoruk, Maja; Czarnecka, Elżbieta (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The authors took up the subject of the RDA and the subject of the level of implementation of this model of cataloging in Polish libraries. The initial part of the article concerns the genesis of the RDA and its relation to the tradition of the Anglo-American principles of AACR cataloging. The authors emphasized the direct relationship with the third edition of the principles and discussed the essence of the revision of the plan of work of the Joint Steering Committee for RDA Development for the years 2005-2009. They also discussed the theoretical foundations of the new standard based on the conceptual models of FRBR and FRAD and on the Declaration of International Cataloging Principles. The rest of this article deals with the characteristics of fundamental changes in the current cataloging practice and their significance for the RDA as an international standard adapted to the digital world and compatible with the Semantic Web. The authors also deal with the subject of RDA implementation in the countries of Europe, the United States, Canada and Australia. The main part of this article is related to the topic of the next stages of RDA implementation in Polish libraries. The authors have attempted to compare the implementation model of the new standard in libraries which cooperate with the National Library and with the NUKAT Centre. They used the method of confronting the relevant bibliographic records of the National Library and NUKAT and confronted the speeches of the National Library and NUKAT Centre representatives at the conference "RDA Standard ? benefits and problems related to its implementation". They analyzed the latest instruction, i.e. "The MARC Format of the 21 bibliographic record for the book" obliging libraries cooperating with the NUKAT Centre to implement subsequent RDA elements. At the end of this article, the authors define the current status of the RDA implementation as a transitional one and underline the difficulty of determining the direction of further changes related to the new cataloging paradigm.
Keywords: RDA (Resource Description and Access); AACR (Anglo-American Cataloguing Rules); biblioteka; Centrum NUKAT; Biblioteka Narodowa; katalogowanie bibliotek; wdrażanie RDA w Polsce; FRBR i FRAD; MARC 21; library; NUKAT Center; National Library; library cataloguing; RDA implementation in Poland